PARENTS INVOLVEMENT IN ESTABLISHING CHARACTER VALUES IN EARLY CHILDHOOD THROUGH MANAGEMENT DEVELOPMENT APPROACH IN TK AR-RAHMAN STM HILIR - Mesiono Mesiono; Poniman Adyanto (PIONIR: JURNAL PENDIDIKAN, 2021)
The purpose of this study was to reveal the involvement of parents in shaping the character values of early childhood through a management development approach at Ar-Rahman Kindergarten, STM Hilir District. The method used in this study is a qualitative approach, so that data collection to subjects and informants is carried out in a comprehensive holistic manner which is an interpretative analysis of the observed phenomena. This qualitative approach is then reflected in the selection of research subjects and informants, as well as in data collection and analysis techniques. The validity of the data is carried out through credibility, transferability, defendability, and confirmability tests. The results showed that, (1) the attitude of the principal, teachers, parents, head of parental involvement, administration, and school caretakers had a positive attitude towards parental involvement in shaping early childhood character values (AUD), and (2 ) Parental support / participation, both the support of thoughts, energy, property, is very supportive in instilling character values for early childhood in Ar-Rahman Kindergarten. In conclusion, the Involvement of Parents in Instilling Character Values for Early Childhood Through a Management Development Approach in Ar-Rahman Kindergarten, STM Hilir District was successful.